Strategy in the Missile Age - Brodie, Bernard, 1910-1978 (Book collections on Project MUSE., 1959)
Reviews the development of modern military strategy to World War II, and considers new problems and new approaches. The study was undertaken by the Rand Corporation as a part of its research program for the United States Air Force.